LITHUANIAN MUSIC PUBLISHING IN THE PERIOD FROM 1990 TO 2013 - KUČINSKAS, DARIUS (Knygotyra, 2014)
The article is dedicated to analyze the Lithuanian music score publishing after the Restitution of Independance of Lithuania (1990). After the specification of the concept of music publishing (publishing of musical compositions, not books about music) it is analyzed according to the main aspects of book analysis – the typology and genres of publications are discussed in it as well as technical and artistic design. Music publishers and music libraries are also assessed and the structure of music community is revealed together with its specific needs. The conclusion is drawn that music publishing in Lithuania has always been a marginal but very important part of a cultural life in a country. On the other hand, there have never been enough prerequisites to establish a long-acting music publishing house because of a small market and weak purchasing power of musical community in Lithuania. Since 1990, about 1400 published music titles have been calculated (according to the data basis of the National Library). The average number of music titles published per year is growing comparing with previous periods. The number of published copies varies from several copies up to 50000. There are only exceptional editions published with an especially small or an extreme number of copies (for example, music repertoire for the National Song Festival is printed with a maximum number of copies). Some small and private publishers started publishing music after 1990. Traditionally they publish only some titles per year. However, they have enlarged music repertoire with different editions according to the type, genre or instrument. The music publisher Jonas Petronis (1911–2005) can be mentioned as an exception – he published more than 100 titles. Today music publishing is regarded as a self-contained process rather than a strategically coordinated one. As a result, there are obvious gaps and uneveness in the current publishing landscape of the Lithuanian musical heritage.